Determination of Human Sapovirus Genotypes Causing Gastroenteritis in Children under Five Years in Baghdad - Mohamed, Nadira Salman; Maaroof, Mohammed Nadher; Hussein, Haider Kadhem (Al-Nahrain Journal of Science, 2017)
Abstract: Sapoviruses (SaVs) may cause acute gastroenteritis (AGE) in young children. To prove the presences of Sapovirus infection in Iraq AGE patients, a total of 200 stool samples from children patients under five years with AGE were collected and screened by reverse transcription real time PCR using specific primers was performed for partial sequencing SaVs capsid and probes cover all Sapovirus genogroups, this was followed by revers transcription PCR and nested PCR using the specific primers. The SaVs partial capsid gene amplicons were sequenced. Partial capsid sequences were blasted with National Center of Information Technology (NCBI) and phylogenetic analysis was conducted using MEGA 6.0 program. Out of the 200 samples tested, 18 (9%) were found SaVs positive. Amplicons were sequenced and only 7 samples were genotyped, 5(5/7) were belonged to the genotype GI.1, 1(1/7) were belonged to the GI.4, and 1(1/7) were belong to the GII.8 .The GI.1 was the dominant strain in Baghdad and the more infected age stage was the children 4 ≤5 years. SaVs was diagnosed in Baghdad in the current study for the first time. These results need more extensive surveillance study to determine the distribution and burden of virus in Iraq community.